Evaluasi Pelaksanaan Permenhub Nomor 18 Tahun 2021 Tentang Pengawasan Muatan Angkutan Barang (Studi Wilayah Kota Manado) - Pinta Simamora; Andreas Lengkong; Arie M. Andes; Herts Taunaumang; Joice Umboh (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
The city of Manado, as one of the centers of economic growth in North Sulawesi, has experienced an increasing demand for transportation in line with population growth and urbanization. This phenomenon presents challenges related to overloaded freight transport, which impacts traffic safety and road infrastructure conditions. This study aims to evaluate the implementation of Permenhub Number 18 of 2021 concerning the supervision of freight transport loads in the city of Manado. The research employed a qualitative approach with a case study method, involving the Head of the Transportation Agency of Manado City and three truck drivers as samples selected through purposive sampling. Data were collected through interviews, field observations, and analysis of related documents. The focus of the research is to identify the effectiveness of the supervision carried out by the Transportation Agency of Manado City and the evaluation measures taken on vehicles with excessive loads. The findings indicate that the supervision of freight transport loads still faces several challenges, including a lack of supporting facilities such as weighbridges and limited monitoring personnel. Efforts made by the Transportation Agency include improving coordination with related institutions, providing education to transportation operators, and imposing sanctions in accordance with regulations.